Liver‐Secreted Extracellular Vesicles Promote Cirrhosis‐Associated Skeletal Muscle Injury Through mtDNA‐cGAS/STING Axis - Xiaoli Fan; Yunke Peng; Bo Li; Xiaoze Wang; Yifeng Liu; Yi Shen; Guofeng Liu; Yanyi Zheng; Qiaoyu Deng; Jingping Liu; Li Yang (Advanced Science, 2025)
Abstract Skeletal muscle atrophy (sarcopenia) is a serious complication of liver cirrhosis, and chronic muscle inflammation plays a pivotal role in its pathologenesis. However, the detailed mechanism through which injured liver tissues mediate skeletal muscle inflammatory injury remains elusive. Here, it is reported that injured hepatocytes might secrete mtDNA‐enriched extracellular vesicles (EVs) to trigger skeletal muscle inflammation by activating the cGAS‐STING pathway. Briefly, injured liver secreted increased amounts of EVs into circulation, which are then engulfed primarily by macrophages in skeletal muscle and subsequently induce cGAS‐STING signaling and its‐mediated inflammatory response in muscles. In contrast, suppression of hepatic EV secretion or STING signaling significantly alleviated cirrhosis‐induced skeletal muscle inflammation and muscle atrophy in vivo. Circulating EVs from cirrhotic patients showed higher levels of mtDNA, and the levels of EV‐mtDNA positively correlated with the severity of liver injury. In injured hepatocytes, mitochondrial damage promoted the release of cytosolic mtDNA and the subsequent secretion of mtDNA‐enriched EVs. This study reveals that injured hepatocyte‐derived EVs induce skeletal muscle inflammation via the mtDNA‒STING axis, while targeted blockade of liver EV secretion or STING signaling represents a potential therapeutic approach for preventing cirrhosis‐associated skeletal muscle atrophy.